The Influence of Intrinsic Motivation, Organizational Commitment, and Transformational Leadership on Employee Performance at CV. Ismie Jaya Tangerang - Prahiawan, Wawan; Sulastri, Sulastri; Arthawati, Sri Ndaru (Management Science Research Journal, 2023)
This research to determine the effect of intrinsic motivation, organizational commitment, and transformational leadership on employee performance. In this study, Intrinsic Motivation, Organizational Commitment, and Transformational Leadership as independent variables and Employee Performance as the dependent variable. This study using sample of 91 respondents with analysis descriptive statistical method. The results showed that partially intrinsic motivation, organizational commitment, and transformational leadership had a positive and significant influence on employee performance.